Analisis Penetapan Harga Pokok Produksi Berdasarkan Metode Full Costing pada Warung Cahaya - M. Ulil Abshor; M. Yogi Ramadana; Rohmatulillah Anggraini; Roudhotus Sa’diyah Al ‘aziziyah; Irma Nur Rosyida; Riska Ela Melisa; Dian Fahriani (Universitas 45 Surabaya, 2025)
In determining the cost of goods produced, two methods can be used, namely the full costing method. In calculating the full costing method, all cost elements are calculated, both variable and fixed. The purpose of this research is to determine the application of the full costing method in determining the selling price. This research uses a qualitative method with a descriptive approach, this research explains the problem in depth, with the data sources used are primary data sources through observation, interviews, and documentation. The technique of analyzing this research is analysis before the field whose data results are temporary, and then analysis during and after the field which will get accurate data. Based on the results of research at Warung Cahaya does not apply the full costing method in calculating the cost of goods produced. The company uses calculations with simple methods and does not calculate all cost elements.